2007
DOI: 10.1111/j.1360-0443.2007.01842.x
|View full text |Cite
|
Sign up to set email alerts
|

Equity of access to treatment, and barriers to treatment for illicit drug use in Australia

Abstract: The study documented significant unmet treatment need and identified several sources of inequity and barriers to treatment that would be amenable to policy and service development. Drug user organizations and peer educators and motivational interventions in primary care settings should be utilized to market the nature and benefits of treatment effectively, and to address the causes of drug users' negative attitudes towards treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 38 publications
2
46
0
2
Order By: Relevance
“…Distance to the clinic has been found to hinder utilisation of services [2224] because of limited transportation abilities [22,25] and travel costs [26] in larger catchment areas. Despite the responsibility of the clinic in Arkhangelsk to treat people in a considerably larger area than the clinic in Tromsø, treated prevalence was higher than for the clinic in Tromsø.…”
Section: Discussionmentioning
confidence: 99%
“…Distance to the clinic has been found to hinder utilisation of services [2224] because of limited transportation abilities [22,25] and travel costs [26] in larger catchment areas. Despite the responsibility of the clinic in Arkhangelsk to treat people in a considerably larger area than the clinic in Tromsø, treated prevalence was higher than for the clinic in Tromsø.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma has negative effects for people with SUD related issues, affecting treatment uptake and completion (Brener, Von Hippel, Von Hippel, Resnick, & Treloar, 2010) impacting upon mental and physical health (Ahern, Stuber, & Galea, 2007). Education for health professionals is one way of reducing such stigma and considering drug treatment is cost effective both on an individual and a community level (Digiusto & Treloar, 2007) The lack of appropriate treatment is further barrier. An Australian study of illicit drug users (male and female) found that 28% of 685 people interviewed were unable to access the treatment they wanted (Digiusto & Treloar, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Education for health professionals is one way of reducing such stigma and considering drug treatment is cost effective both on an individual and a community level (Digiusto & Treloar, 2007) The lack of appropriate treatment is further barrier. An Australian study of illicit drug users (male and female) found that 28% of 685 people interviewed were unable to access the treatment they wanted (Digiusto & Treloar, 2007). Barriers included; no drug treatment in their area, long waiting lists, lack of support from health care workers, inappropriate treatment, travel problems, treatment cost and treatment that did not accommodate children (Digiusto & Treloar, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otras barreras provienen de la organización asistencial: complejidad en los mecanismos de admisión a tratamiento de estos pacientes, escasa empatía por esta patología, saturación de los dispositivos asistenciales, desconocimiento de los servicios de tratamiento y dificultades de accesibilidad geográficas [2][3][4][5][6][7] . Y finalmente las actitudes negativas de los trabajadores de la salud respecto de los trastornos adictivos [8][9][10][11][12][13][14][15][16][17][18] pueden influir no sólo en la calidad de la atención 16,17,19 sino también dificultar el acceso al tratamiento de estos pacientes 20 .…”
Section: Introductionunclassified